1987
DOI: 10.1051/rnd:19870604
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of rapeseed meal. 5. Effects of sinapine and other phenolic compounds on food intake and nutrient utilization in growing rats

Abstract: Summary. Six groups of 10 growing rats each were fed ad libitum for 15 days one of six diets : diet A, rapeseed (3.80 g of sinapine/kg DM) ; diet B, ethanol/water-extracted rapeseed (0.48 g of sinapine) ; diet C, control diet ; diet G, control diet + 3.74 g of extracted sinapine ; diet H, control diet + 3.72 g of sinapine + other phenolic compounds ; or diet I, control diet + the hydrolysis products of sinapine and other phenolic compounds.During the first 8 days, the dry matter intake and live weight gain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This variation in time cannot be explained by the poor palatability of the rapeseed meal due to the presence of sinapine since the rats were adapted progressively to the diets and their performance improved between days 3 and 8. It was shown that rats adapt to the presence of sinapine in the diet within one week (Vermorel, Hocquemiller and Evrard, 1987). Moreover, Lee, Pittam and Hill (1984) showed that a reduction in feed intake by growing pigs receiving rapeseed was due to the presence of glucosinolates rather than to sinapine or tannins.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in time cannot be explained by the poor palatability of the rapeseed meal due to the presence of sinapine since the rats were adapted progressively to the diets and their performance improved between days 3 and 8. It was shown that rats adapt to the presence of sinapine in the diet within one week (Vermorel, Hocquemiller and Evrard, 1987). Moreover, Lee, Pittam and Hill (1984) showed that a reduction in feed intake by growing pigs receiving rapeseed was due to the presence of glucosinolates rather than to sinapine or tannins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not known whether snail meal has any features that would make it less palatable to rainbow trout, and the lack of literature hinders discussion of the issue in this paper. However, in some studies, it has been determined that phenolic compounds in certain feed components affect the alimentary preferences of the consuming animal (Addisu, 2016; Dossou et al., 2018; Valiela & Rietsma, 1984; Vermorel et al., 1987). In this study, 11.5 mg/g total phenolic substance was found in the dietary snail meal used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, natural antioxidants are attracting more attention due to safety concerns of synthetic antioxidants (Shahidi and Ambigaipalan, 2015). Previously, few studies focused on phenols contained in rapeseed oil (Koski et al, 2002(Koski et al, , 2003Siger et al, 2008), compared to its meal (Vermorel et al, 1987;Amarowicz et al, 2000;Vuorela et al, 2004;Khattab et al, 2013;Szydłowska-Czerniak and Tułodziecka, 2014), since a large proportion of phenolic compounds is still in rapeseed meal after seed oil pressing (Naczk and Amarowicz, 1998).…”
Section: Introductionmentioning
confidence: 99%